2017
DOI: 10.1007/s00415-017-8602-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of N-terminal pro-brain natriuretic peptide in evaluating the prognosis of patients with intracerebral hemorrhage

Abstract: A prognostic biomarker that can provide a good prediction of prognosis in patients with intracerebral hemorrhage (ICH) would be beneficial in guiding the initial management decisions in the setting of ICH. N-terminal pro-brain natriuretic peptide (NT-proBNP) is a biomarker of prognosis in patients with cardiovascular disease and ischemic stroke. However, the prognostic role of NT-proBNP in patients with spontaneous ICH is still a controversial issue. This study aimed to determine the prognostic value of NT-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Hemorrhagic transformation could impact subsequent antiplatelet treatments; severe symptomatic intracranial hemorrhage could be associated with a mortality rate of up to 50% (National Institute of Neurological Disorders and Stroke rt-Pa Stroke Study Group, 1995;Yaghi et al, 2014). The association between elevated NT-proBNP levels and intracerebral hemorrhage has been demonstrated in previous studies (Di Castelnuovo et al, 2019), and elevated NT-proBNP levels were associated with a larger volume of hematoma and poor outcomes (Li et al, 2017(Li et al, , 2018. Our findings demonstrate that NT-proBNP levels are independently associated with hemorrhagic transformation in patients with stroke who have undergone intravenous thrombolysis.…”
Section: Discussionmentioning
confidence: 91%
“…Hemorrhagic transformation could impact subsequent antiplatelet treatments; severe symptomatic intracranial hemorrhage could be associated with a mortality rate of up to 50% (National Institute of Neurological Disorders and Stroke rt-Pa Stroke Study Group, 1995;Yaghi et al, 2014). The association between elevated NT-proBNP levels and intracerebral hemorrhage has been demonstrated in previous studies (Di Castelnuovo et al, 2019), and elevated NT-proBNP levels were associated with a larger volume of hematoma and poor outcomes (Li et al, 2017(Li et al, , 2018. Our findings demonstrate that NT-proBNP levels are independently associated with hemorrhagic transformation in patients with stroke who have undergone intravenous thrombolysis.…”
Section: Discussionmentioning
confidence: 91%
“…After eliminating duplications, 1,125 articles were retained, of which 1,097 were excluded due to irrelevant titles and abstracts. The full texts of the remaining 28 articles were reviewed for inclusion, and 10 studies (18)(19)(20)(25)(26)(27)(28)(29)(30)(31) fulfilled the inclusion criteria for systematic review. The detailed process of study screening is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Five studies (18-20, 26, 28) including 980 participants provided the data on all-cause mortality outcome, indicating a correlation with BNP/NT-proBNP level. Among them, four studies (18,19,26,28) found consistently higher levels of BNP/NT-proBNP in non-survivors compared with survivors (range of means: 99.9-1986.48 vs. 32.4-432.38 pg/ml; P < 0.05). Three studies reported multivariate logistic regression analysis to assess risk estimate.…”
Section: All-cause Mortalitymentioning
confidence: 99%
See 2 more Smart Citations